Artificial intelligent technology and challenges for intellectual property rights of invention in Vietnam - Hai, Nguyen Manh; Hieu, Bui Trung; Tuan, Nguyen Quang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
Over the past years, the development of Artificial Intelligence has been making strong impacts on all aspects of the world’s economy and society, including legal systems, development policy in general and the law on intellectual property rights in particular. However, research on the impact of Artificial Intelligence technology towards intellectual property policy and law is a new topic that only gets attention in recent years. This is also an immense topic for a sole article. Therefore, this study will focus on analyzing some challenges which Artificial Intelligence technology brings to intellectual property rights on inventions; thereby proposing several orientational solutions, contributing to the improvement of the intellectual property legal system for Vietnamese inventions. Code: 210702201 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">